Global and Regional Business Cycles. Shocks and Propagations - Leif Anders Thorsrud (Norges Bank, 2013)
We study the synchronization of real and nominal variables across four different regions of the world, Asia, Europe, North and South America, covering 32 different countries. Employing a FAVAR framework, we distinguish between global and regional demand and supply shocks and document the relative contributions of these shocks to explaining macroeconomic fluctuations and synchronization. Our results support the decoupling hypothesis advanced in recent business cycle studies and yields new insights regarding the causes of business cycle synchronization. In particular, global supply shocks cause more severe activity fluctuations in European and North American economies than in Asian and South American economies, whereas global demand shocks shift activity in the different regions in opposite directions at longer horizons. Furthermore, demand shocks play a larger role than that found in related studies. Finally, only innovations to the Asian activity and price factors have significant spillover effects on shared global factors, demonstrating the growing importance of Asia in the global economy.
hdl:11250/2496701
Keywords: C11; C38; F41; F44; 330; business cycles; factor model; globalization; international macro